Characterization of wheat (Triticum aestivum L.) accessions using morpho-physiological traits under varying levels of salinity stress at seedling stage - Ahmed, Hafiz Ghulam Muhu-Din; Zeng, Yawen; Raza, Humayun; Muhammad, Dur; Iqbal, Muhammad; Uzair, Muhammad; Khan, Mueen Alam; Iqbal, Rashid; EL Sabagh, Ayman (Frontiers in Plant Science, 2022)
Abiotic stress is one of the major hurdles for the wheat production. The world population is increasing continuously. It is very difficult to feed the population because one third of world population consumed the wheat (Triticum aestivum L.) as a staple food. Among all the abiotic stresses salinity is one of the major problems for the cultivation of wheat because the wheat is sensitive to the salinity stress. For this purpose, an experiment was conducted at the Department of Plant Breeding and Genetics, Islamia University of Bahawalpur using the complete randomized design with four replications to determine the selection criteria for salinity tolerant germplasm on the base of physiological and morphological seedling traits. Three levels of salts solution 4 dSm-1, 8 dSm-1, 12 dSm-1 applied and then the performance of different germplasm under these three salinity stress levels was observed and found that leaf water content and relative water content are correlate with each other. However, selection on the base of these traits increased the performance of other characters. From the results of Principal Component (PC) analysis, first five PCs were indicated a substantial genetic variation from the total 14 principal component (PCs). Theses PCs showed 75%, 73%, 65.324% and 65.162% total variation under normal, salinity level 4 dSm-1, 8 dSm-1, 12 dSm-1 respectively. Stomatal conductance, fresh shoot weight and fresh root weight, dry shoot weight and dry root weight were not significant and negatively associated with all other traits studied, except for relative water and leaf water content. Overall, the results suggest that selection based on wheat leaf content and relative water content at the seedling stage would genetically improve salinity tolerance. Genotypes with good performance under salt stress conditions may be useful in future wheat breeding programs and in early breeding for the suggested traits and will be effective in developing high yielding and salt tolerant wheat varieties.